(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2007)
The study of real adoption impact (RAI) measure of technologies on tomato production at farmers’ level revealed that there was a positive and significant relationship between yield and the values of RAI which was calculated utilizing the degrees of deviations between standard recommendations for tomato and their level of application at farmers’ field. This study implies that the higher value of RAI resulting from more proper adoption of tomato technologies would give higher yield. It was found from the estimated model that 1 percent higher value of RAI would give more than 4 percent greater tomato yield. From this model it was also found that the expected yield gap and observed yield gap of tomato were much greater than that of estimated yield and observed yield indicating a scope to increase the yield of tomato. These results exclusively indicate to a situation where tomato farmers were in complete knowledge of the technologies but they were not using recommended doses of inputs and also management practices properly and completely in production system. As a result they could not reap the yield like research station yield of 80 t/ha. The farmers were getting about 1/4th yield on an average and made a sharp and big yield gap of tomato between on station and farmers’ field. It calls for an intensive extension work focused on tomato technologies and timely support with required inputs with a view to minimize the yield gap for national interest. Bangladesh J. Sci. Ind. Res. 42(1), 15-28, 2007